The autonomous city: towards a critical geography of occupation - Vasudevan, Alexander (SAGE, 2015)
This paper explores the recent resurgence of occupation-based practices across the globe, from the seizure of public space to the assembling of improvised protest camps. It re-examines the relationship between the figure of occupation and the affirmation of an alternative ‘right to the city’. The paper develops a critical understanding of occupation as a political process that prefigures and materializes the social order which it seeks to enact. The paper highlights the constituent role of occupation as an autonomous form of urban dwelling, as a radical politics of infrastructure and as a set of relations that produce common spaces for political action.